ANALISIS KUALITAS PELAYANAN, KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS KONSUMEN PADA WARUNG BAMBU DI KOTA TANAH GROGOT - Aswan Ramadani; Nuraini; Titiek Aryati Prihati; Fathur Rahman S. (JURNAL ILMIAH EDUNOMIKA, 2026)
The main focus of this study is to find out how much contribution is made by the factors of service quality, product quality, and price in shaping consumer loyalty to bamboo stalls in the city of Tanah Grogot with a sample of 100 respondents based on certain criteria. This study uses a quantitative approach that is associative explanatory in nature. The researcher collected primary data by distributing a questionnaire that was measured using a Likert scale of 1-5 (from Strongly Disagree to Strongly Agree). The research instrument will be tested for feasibility first through the Validity Test (Pearson Product Moment correlation) and the Reliability Test (Cronbach's Alpha) to ensure that the questionnaire is on target and consistent. The main data analysis method applied in this study is Multiple Linear Regression Analysis. In order to ensure the validity of the regression model, the research data must meet the validity and reliability. The results of the study show that service quality, product quality, and price significantly affect consumer loyalty. Among the three variables, the price factor was found to have the most dominant influence on consumer loyalty. Based on the results of the calculation, the R value (correlation coefficient) of 0.687 is at the level of a strong relationship (0.600 – 0.799) between the bound variable and the independent variable. Based on the results of the R2 calculation, the determination coefficient was 0.472 or the moderate level of influence between the free variable and the bound variable was 47.2%, while the remaining 52.8% was influenced by other variables that were not included in this study. Keywords : Service Quality, Product Quality, Price, Consumer Loyalty